Widespread severe acute respiratory coronavirus virus 2 (SARS-CoV-2) laboratory surveillance program to minimize asymptomatic transmission in high-risk inpatient and congregate living settings - Jatt, Lauren P. (Infect Control Hosp Epidemiol, 2020)
We describe a widespread laboratory surveillance program for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) at an integrated medical campus that includes a tertiary-care center, a skilled nursing facility, a rehabilitation treatment center, and temporary shelter units. We identified 22 asymptomatic cases of SARS-CoV-2 and implemented infection control measures to prevent SARS-CoV-2 transmission in congregate settings.